(Water) bottles and (street) barricades: the politicisation of lifestyle-centred action in youth climate strike participation. (3rd July 2022) - Zamponi, Lorenzo; Baukloh, Anja Corinne; Bertuzzi, Niccolò; Chironi, Daniela; della Porta, Donatella; Portos, Martín
ABSTRACT: In resisting climate change, to what extent can lifestyle forms of activism be considered to be political? What are their determinants and to what extent do they differ from the determinants of other forms of action? What role do generational factors play? Does the centrality of lifestyle changes for young participants translate into a disaffection towards more traditional forms of action? This article explores the forms of action adopted by participants in two Fridays For Future (FFF) strikes, focusing on the repertoires of action of (young) climate justice protesters. We draw on protest survey data covering the FFF demonstrations held in 15 European countries in March and September 2019. Starting from a sharp generational contrast between the importance given to individual lifestyle changes in addressing the climate emergency, we investigate whether this results in significant generational differences in the choice of the repertoires of action. Challenging the vision of young people as 'disaffected citizens', it is demonstrated that young protesters do not participate less in claim-based action than older cohorts. Furthermore, a process of politicisation can be seen to be unfolding that leads to increased commitment in both lifestyle and political forms of participation – at least among active milieus.